Studies of mortuary value system and its behavior: Columbarium Niche burial and natural burial as study cases in Taiwan - KUO-CHU YANG; HSIAO-PING HUNG; FU-CHUAN HSU; YIN-AN CHEN (Journal of Advanced Research in Social Sciences and Humanities, 2021)
Aim: This research aims to examine the contemporary Taiwanese mortuary practices, identifies the disconnect between the country’s mortuary value system and its actual practice, and delves into the connections between the two and grief support. The government of Taiwan’s research findings will be used as a basis for developing funeral policy. Method: Secondary data analysis, in-depth interviews, and thematic data analysis were used to compile this report. Participants in this study were relatives who have suffered a recent death within the last three years. In total, there are thirteen people taking part. 8 people chose to be interred in a columbarium niche, while 5 people went the natural route. Findings: Lineal relatives are the backbone of the funeral planning strategy;